Genome-Wide Association Study of Body Conformation Traits by Whole Genome Sequencing in Dazu Black Goats - Bowen Gu; Ruifan Sun; Xingqiang Fang; Jipan Zhang; Zhongquan Zhao; Deli Huang; Yuanping Zhao; Yongju Zhao (Animals, 2022)
Identifying associations between genetic markers and economic traits has practical benefits for the meat goat industry. To better understand the genomic regions and biological pathways contributing to body conformation traits of meat goats, a genome-wide association study was performed using Dazu black goats (DBGs), a Chinese indigenous goat breed. In particular, 150 DBGs were genotyped by whole-genome sequencing, and six body conformation traits, including body height (BH), body length (BL), cannon circumference (CC), chest depth (CD), chest width (CW), and heart girth (HG), were examined. In total, 53 potential SNPs were associated with these body conformation traits. A bioinformatics analysis was performed to evaluate the genes located close to the significant SNPs. Finally, 42 candidate genes (e.g., PSTPIP2, C7orf57, CCL19, FGF9, SGCG, FIGN, and SIPA1L) were identified as components of the genetic architecture underlying body conformation traits. Our results provide useful biological information for the improvement of growth performance and have practical applications for genomic selection in goats.